2022
DOI: 10.1002/ase.2169
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of online anatomy teachers: A neglected study population struggles with the invisible student

Abstract: Distance education describes the mechanism by which students learn without in-person events and study at a time and place of their choosing (Bates, 2005). Given the necessary role of technology in modern day distance education, Moore and Kearsley (2012) describe distance education as "teaching and planned learning by which the teaching normally occurs in a different place from learning, requiring communication through technologies as well as special institutional organization." Simonson et al. (2011) elaborate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 68 publications
2
3
0
Order By: Relevance
“…Delivering teaching purely online also resulted in an ‘invisible student’ scenario, where students could choose not to use cameras and become faceless. Such challenges have been reported elsewhere ( Attardi et al, 2022 ). Being unable to assess engagement and adjust teaching strategies accordingly affects teaching relationships and demonstration of technical subject matter components ( Attardi et al, 2022 ).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Delivering teaching purely online also resulted in an ‘invisible student’ scenario, where students could choose not to use cameras and become faceless. Such challenges have been reported elsewhere ( Attardi et al, 2022 ). Being unable to assess engagement and adjust teaching strategies accordingly affects teaching relationships and demonstration of technical subject matter components ( Attardi et al, 2022 ).…”
Section: Discussionsupporting
confidence: 54%
“…Such challenges have been reported elsewhere ( Attardi et al, 2022 ). Being unable to assess engagement and adjust teaching strategies accordingly affects teaching relationships and demonstration of technical subject matter components ( Attardi et al, 2022 ).…”
Section: Discussionsupporting
confidence: 54%
“…One of the most important reasons for limited interaction is the lack of “real” eye contact, an essential pedagogical tool, in online education [ 36 ]. Another reason that disrupted the interaction was that the academic staff and students came together only on an online platform, resulting in an “invisible student” who could choose not to use a camera [ 32 , 37 ]. Similarly, in the study of Casacchia et al [ 38 ], academic staff complained about reduced interaction with students during lessons.…”
Section: Discussionmentioning
confidence: 99%
“…Problems with time management stemmed from preparing courses for a new teaching environment and combining private life and business life in the same physical space. According to the participants, preparation time for online courses took more time, as reported in the literature [ 37 , 39 ]. The lack of boundaries between work and home was a challenge for time management for both male and female participants.…”
Section: Discussionmentioning
confidence: 99%
“…The review also noted several limitations of digital education, such as inconsistent quality control and inadequate teacher training in online education delivery [10]. Indeed, many educators need more experience and expertise in online course design and content creation [11][12][13]. A study evaluating 26 faculty members at a large academic institution in the United States (US) found that many of them felt inhibited by technological challenges, unfamiliarity with the needed resources, and concerns about legal implications, such as violating copyright laws [14].…”
Section: Introductionmentioning
confidence: 99%